Changing the focus of locus (of control): A targeted review of the locus of control literature and agenda for future research. (23rd March 2018) - Galvin, Benjamin M.; Randel, Amy E.; Collins, Brian J.; Johnson, Russell E.
Summary: Locus of control—a fundamental individual difference variable that reflects individuals' beliefs about the degree of control they have over events in their lives—has been formally studied for more than 50 years. Early scholarship demonstrated that locus of control was a key predictor of various work‐related outcomes, ranging from job attitudes and affect to motivation and behavior. Despite this evidence, the majority of contemporary organizational research has moved away from examining locus of control as an independent construct. Instead, locus of control is now commonly examined as a component of core self‐evaluation. However, recent research suggests that locus of control is in fact an independent, distinct concept and that core self‐evaluation research should continue without incorporating locus of control in future work. This presents an opportunity to theoretically review locus of control as a distinct construct and explicate its salient characteristics. Accordingly, this review aims to further clarify the construct of locus of control, provide a foundation upon which research may build, and elucidate fruitful avenues for future research.